Fractured pedagogy: the design and implementation fault line in architectural knowledge - a conceptual and historical analysis - Carter, Francis (School of Education, 2020)
There appears to be a gap in architectural knowledge between design theory and implementation practice which is difficult to bridge in teaching, learning and work. As evidence of the existence of this gap two sources of data are contrasted: exhibition catalogues which convey what individual architects say to each other about their work, and official reports which convey what institutional representatives of the organised profession say about failures in the work of architects. These data sets are contradictory, reinforcing the possibility of a fault-line between design knowledge and implementation. The question then arises as to whether this tension in professional knowledge in the field of production is reflected in the pedagogisation of the knowledge, reinforced through its transmission. As the architectural curriculum in Commonwealth countries has a generic format, this generic curriculum is analysed next, in terms of Bernstein's concepts of classification/ framing, and integration I collection. The analysis is ambiguous, as both strong and weak criteria co-exist with dual coding, complicated by the horizontality and tacit nature of spatial design knowledge on the one hand, and the extent of regionalised knowledge on the other which recontextualises contradictory knowledge systems from sources in arts and sciences. Tacit implementation knowledge sits uncomfortably in this mix as a largely segmental horizontal discourse. To understand the default pattern in this pedagogy more clearly, the research then tracks back to the initial definition of the knowledge system at the time of the formation of the modern profession. In this analysis Bernstein's pedagogic device is used as the framework for locating and unraveling the historic data in terms of the production and recontextualisation of knowledge, distributive rules and power relations between agents. The history maps neatly onto this theoretical model, confirming in-built tensions in the knowledge system which marginalise knowledge of implementation and which construct a professional consciousness centered around spatial imagination primarily and technical innovation secondarily. The research is thus an initial attempt at a historical analysis of a region of professional knowledge.